Ferulic Acid Prevents Angiogenesis Through Cyclooxygenase-2 and Vascular Endothelial Growth Factor in the Chick Embryo Chorioallantoic Membrane Model - EKOWATI, Juni (Turk J Pharm Sci, 2020)
OBJECTIVES: This study was designed to verify the antiangiogenic activity of ferulic acid (FA) and its potency to inhibit cyclooxygenase-2 (COX-2) and vascular endothelial growth factor (VEGF) expression in the chorioallantoic membrane (CAM) model. Moreover, we verified its mechanism of action by docking the molecule on COX-2, tyrosine kinase, and VEGF-2 proteins in silico. MATERIALS AND METHODS: An antiangiogenesis assay of FA at doses of 30, 60, and 90 μg was performed using the CAM of chicken eggs that were 9 days old and stimulated by 60 ng of basic fibroblast growth factor. Celecoxib (60 μg) was used as the reference drug. The inhibitory activity on VEGF and COX-2 expression was determined by immunohistochemistry assay. Molecular docking of FA was accomplished by Molegro Virtual Docker program ver. 5.5 on COX-2 enzyme (PDB ID 1CX2), tyrosine kinase receptor (PDB ID 1XKK), and VEGF-2 receptor (PDB ID 4ASD). RESULTS: FA at doses of 30, 60, and 90 μg significantly prevented angiogenesis in the CAM model, which was represented as inhibitory activity against endothelial cells of blood vessels (42.6-70.7%) and neovascularization (43.0-86.6%). The inhibitory activity of FA against VEGF expression was stronger than its action on COX-2 expression. Molecular docking on VEGF-2 receptor resulted in an RS value of FA of -73.844 kcal/mol and for celecoxib it was -94.557 kcal/mol. The RS value on tyrosine kinase of FA was -84.954 kcal/mol, while on celecoxib it was -93.163 kcal/mol. Docking on COX-2 receptor gave an RS value of FA of -73.416 kcal/mol, while for celecoxib it was -118.107 kcal/mol. CONCLUSION: Reductions in VEGF-2 and COX-2 expression due to treatment with FA at the dose range 30-90 μg appeared to be related to angiogenesis inhibition, which was shown by two parameters, namely inhibition of neovascularization and endothelial cell growth in blood vessels. It was concluded that FA is a promising antiangiogenic therapeutic agent especially at the early stage, and this activity can arise from inhibitory action on COX-2 and VEGF-2 proteins.